The benefits of Gametherapy in patients with Alzheimer´s Disease (Research, Society and Development, 2021)
Objective: To investigate the benefits of using Game therapy, showing the functional and cognitive improvement of patients with Alzheimer´s disease. This is an integrative review. The methodology was divided into three stages for better organization and formation of the research. Methodology: A total of 22 articles were selected through the SciElo, PubMed, LILACS, PeDro and Academic Google databases, using specific descriptors. Results: In general, the studies showed that there were gains in gait pattern, agility, mobility, motor coordination, learning new information, constructive capacity and memory of patients who underwent the use of Gametherapy through various virtual games, causing there was a better acceptance of treatment of the disease and providing effective results. Conclusion: It is concluded that the use of Gametherapy in physical therapy intervention provides relevant gains in improving the functional and cognitive of patients with Alzheimer disease. However, specific studies are needed that can measure the results achieved with the use of a given topic.